Kajian Pakaian Ihram Laki-laki Perspektif Hadis - Eca Dwi Yandra (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about Ihram. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about Ihram in the history of Bukhari No. 5348. The results and discussion of this study indicate that the status of authentic quality hadith fulfills the qualifications of maqbul ma'mul bih for Islamic practice. This study concludes that the hadith narrated by Bukhari No. 5348 is relevant for Islamic symbols that men are not allowed to wear sewing clothes during Ihram.